Survival analysis as a methodological alternative to estimate probabilities of default of corporate credit debtors and large companies in Peru - Uriarte Cáceres, Fátima (2017)
The calculation of probabilities of default can be improved by incorporating additional variables that can be predicted and which are associated with changes in the debtors' financial situation and the economic situation. The inclusion of these variables is possible through the use of survival analysis. In the present paper, an application of the Cox proportional hazards model is performed to identify some explanatory variables of the risk of default of new corporate credit debtors and large companies. The characteristics of the debtor (economic sector, indebtedness, profitability, size of the company); credit (initial loan, percentage in foreign currency, percentage of guarantees); together with entity grouping and business confidence index were identified as risk factors for non-compliance in the payment of corporate and large companies loans.